Crystal structure of chlorido(2-methylquinolin-8-olato-κ2N,O)-bis(4-tolyl-κC)tin(IV), C24H22ClNOSn - Lee, See Mun *; Lo, Kong Mun *; Tiekink, Edward R. T. * (De Gruyter Open, 2020)
C24H22ClNOSn, monoclinic, P21/c (no. 14), a = 13.7584(1) Å, b = 13.5542(1) Å, c = 13.0912(1) Å, β = 115.778(1)°, V = 2198.36(3) Å3, Z = 4, Rgt(F) = 0.0170, wRref(F2) = 0.0448, T = 100(2) K.